What’s in a Japanese kawaii ‘cute’ name? A linguistic perspective - Kumagai, Gakuji (Frontiers in Psychology, 2022)
While the concept termed as kawaii is often translated into English as ‘cute’ or ‘pretty’, it has multiple connotations. It is one of the most significant topics of investigation in behavioural science and Kansei/affective engineering. This study aims to explore linguistic (phonetic and phonological) features/units associated with kawaii. Specifically, it examines, through experimental methods, what kinds of phonetic and phonological features are associated with kawaii, in terms of the following three consonantal features: place of articulation, voicing/frequency, and manner of articulation. The results showed that the features associated with kawaii are: [labial], [high frequency], and [sonorant]. The factors associated with kawaii may include the pouting gesture, babyishness, smallness, femininity, and roundness. The study findings have practical implications due to their applicability regarding the naming of anime characters and products characterised by kawaii.